The analysis of factors influencing the delay of the treatment by patients with the chest pain - Ziółkowska, Krystyna; Paciorek, Przemysław (Polish Journal of Public Health, 2009)
Aim of work. The analysis and evaluation of the delay in treatment of acute coronary syndrome, depending on the location of the call. Materials and methods. The data have been collected on the basis of medical documentation of Ambulance Station in Słupsk. The analysis concerned 822 cards of emergency actions. Results. The shortest time lapse between notifi cation and arrival of the emergency team in the town and outside the town was 4 minutes, the longest in the town was 29 minutes and the shortest – 37 minutes. In the town an ambulance most often arrived within 6 minutes, outside the town within 14 minutes. The shortest time of arrival of a patient from urban area to hospital was 18 minutes, the longest was 69 minutes. The shortest time from outside the urban area was 26 minutes and the longest 78 minutes. Patients arrived at hospital from the town most often within 28 minutes, from outside – within 64 minutes. Conclusions. Almost half of the patients from outside urban area waited for the arrival of an ambulance over 20 minutes and appeared at hospital after 60 minutes. Over three quarters of patients from the town were driven to hospital within 30-40 minutes. The patients hesitated with the call to rescue ambulance service almost for 2 hours which resulted in delay of treatment.